Invasive Therapies for Primary Postpartum Haemorrhage: A Population-based Study in France. Issue 1 (March 2017) - Kayem, G.; Dupont, C.; Bouvier-Colle, M.H.; Rudigoz, R.C.; Deneux-Tharaux, C.
Abstract : ( BJOG. 2016;123:598–605) Despite continuing improvements in obstetric practice, hemorrhage remains a major cause of maternal mortality even in developed countries.